Experimental two way quantum key distribution with weak+vacuum decoy state - Abdul Khir , Mohd Fared; Mohd Zain, Mohd Norzaliman; Iskandar , Bahari; ., Suryadi; Shaari, Sahbudin (2012)
We report a free space based experimental demonstration of a two way Quantum Key Distribution protocol withweak+vacuum decoy state. By utilizing a different key rate formula a better maximum secure distance closer to the theoretical infinite was achieved.